Shrub encroachment shifts the bioclimatic limit between marcescent and sclerophyllous oaks along an elevation gradient in west-central Spain - Madrigal-González, Jaime; García-Rodríguez, José a.; Zavala, Miguel A. (Journal of Vegetation Science, 2014)
Questions (1) Does shrub encroachment affect the regeneration of two contrasting species of oak along an elevation gradient in the west-central Iberian Peninsula? (2) Do different nurse shrubs have any relevant species-specific effects along the gradient? (3) Does shrub encroachment affect the location of the bioclimatic limit between these two oak species along the elevation gradient? Location Twelve sites distributed from the Arribes del Duero plains to the Sistema Central mountains (Salamanca province, Spain). Methods We measured the regeneration of two contrasting oak tree species (Quercus ilex subsp. ballota Samp - sclerophyllous, Q.pyrenaica Willd - marcescent) as the relative percentage cover of seedlings and saplings (<1.3-m high) in plots 10m in diameter distributed in stands of different age. We fixed the bioclimatic limit at 50% relative proportion of species in each plot, i.e. whether one species was more abundant than the other in a plot. Shrub stand age was estimated by counting growth rings in the principal stems of the oldest shrubs in a plot. We fitted generalized linear mixed models to analyse the effects of elevation, specific nurse shrub and shrub stand age on regeneration and the probability of one species being more abundant than the other. Results The regeneration and relative proportion of Q.ilex (sclerophyllous) decreased with elevation. Regeneration did not vary with shrub encroachment, although the relative proportion increased notably in the youngest stands. In turn, regeneration and relative proportion of Q.pyrenaica (deciduous) significantly increased towards the upper sites and mature shrub stands. We found no evidence of specific nurse shrub effects on regeneration or the probability of one species being more abundant than the other in either of the two species of oak. Conclusions The bioclimatic limit between the two contrasting species of oak shifted with shrub stand age along the elevation gradient. Land practices preventing shrub encroachment can thus indirectly shift this limit towards higher elevations. The effects of shrubs may be critical in resolving the climatic and land-use effects on elevation shifts of species under changing conditions in bioclimatic transitions.
Keywords: Bioclimatic limit; Elevation gradient; Oak trees; Regeneration; Shrub encroachment; Species distribution

Acorn Selection by the Wood Mouse Apodemus sylvaticus: A Semi-Controlled Experiment in a Mediterranean Environment. - Rosalino, Luís Miguel; Nóbrega, Filomena; Santos-Reis, Margarida; Teixeira, Generosa; Rebelo, Rui (Zoological science, 2013)
Fruits are highly important food resources for mammals in Mediterranean Europe, and due to the dominance of oaks (Quercus sp.), acorns are among those used by a vast array of species, including rodents. The metabolic yield of acorn intake may determine a selection pattern: preference for fat, carbohydrate, and consequently energy-rich fruits; or avoidance of fruits containing high concentrations of secondary chemical compounds (e.g., tannic acid). We studied the acorn feeding selection pattern of wood mice (Apodemus sylvaticus) inhabiting a mixed oak woodland, southwest Portugal, using an experiment conducted in an open-air enclosure. We tested which variables associated with the wood mouse (e.g., sex) and acorns (e.g., size and nutrient content) from three oak species (holm Q. rotundifolia, Portuguese Q. faginea and cork Q. suber oak) could be constraining acorn consumption. Our results indicate that wood mice are selecting acorns of the most common oak species (Q. suber), probably due to their previous familiarization with the fruit due to its dominance in the ecosystem but probably also because its chemical characteristics (sugar contents). Rodent gender and acorn morphology (width) are also influential, with females more prone to consume acorns with smaller width, probably due to handling limitation. This selective behaviour may have consequences for dispersion and natural regeneration of the different oak species.
From Duplicate 1 (
Keywords: Oak trees; Q. rotundifolia; Q. suber; Quercus faginea; rodents; seed consumption; seed dispersal

Electron microscopy and composition of raw acorn starch in relation to in vivo starch digestibility - Cappai, Maria Grazia; Alesso, Giuseppe Andrea; Nieddu, Giuseppa; Sanna, Marina; Pinna, Walter (Food & Function, 2013)
The structure and composition of starch play an important role as co-factors affecting raw starch digestibility: such features were investigated in raw acorn starch from the most diffused oak trees in the Mediterranean basin. A total of 620 whole ripe acorns from Holm (Quercus ilex L., n = 198), Downy (Quercus pubescens Willd., n = 207) and Cork (Quercus suber L., n = 215) oaks sampled on the Sardinia Isle (40[degree] 56[prime or minute] 0[prime or minute][prime or minute] N; 9[degree] 4[prime or minute] 0[prime or minute][prime or minute] E; 545 m above the mean sea level) in the same geographical area, were analyzed for their chemical composition. The starch contents ranged between 51.2% and 53.5% of dry matter. The starch granules displayed a spheroid/ovoid and cylindrical shape; on scanning electron microscopic (SEM) analyses, a bimodal distribution of starch granule size was observed both for Holm and Cork oak acorns, whereas the starch granules of Downy oak acorns showed diameters between 10.2 and 13.8 [small mu ]m. The specific amylose to amylopectin ratio of acorn starch was 25.8%, 19.5% and 34.0% in the Holm, Downy and Cork oaks, respectively. The 13C Nuclear Magnetic Resonance (NMR) signal analysis displayed a pivotal spectrum for the identification of the amylose peaks in raw acorn starch, as a basis for the amylose to amylopectin ratio determination.
Key words added by Adriana SilvaKey words added by Adriana SilvaThe following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: amilose; Mediterranean basin; Oak trees

Forest structure and understory diversity in Quercus pyrenaica communities with different human uses and disturbances - Tárrega, Reyes; Calvo, Leonor; Marcos, Elena; Taboada, Ángela (Forest Ecology and Management, 2006)
The aim is to compare the diversity of the understory in Quercus pyrenaica communities according to the type of human intervention (grazing, obtaining wood or ﬁrewood, forest ﬁres). This interaction results in a modiﬁcation of the characteristics of the arboreal layer and shrub cover. Four types of oak communities were selected, each with ﬁve replicates: communities with a high density of shrubby oak (oak shrublands), open woodlands (‘‘dehesas’’), mature oak woods with abundant woody biomass in the understory and mature oak woods with little woody biomass in the understory. In each study site, we quantiﬁed the size of the trees (height, trunk perimeter and crown diameter) and their density, woody cover in the understory and species richness as well as diversity using the Shannon index, on both a small scale (per m 2 ) and for the total of each community. A clear difference was observed between the dehesas and the oak shrublands, the two community types with higher human intervention (the dehesas, with sustainable use for grazing and the oak shrublands, the most degraded due to repeated ﬁres), in the principal components analysis carried out with these variables. The other two community types, considered more mature forests, presented an intermediate location on the principal components analysis. However, there was no clear relationship between the different community types and the diversity values. No differences were observed in total species richness, except that the number of annuals being signiﬁcantly higher in the dehesas. Nor was it possible to detect any differences using the Shannon index, except for the oak shrublands which, although with a great variability among them, had a lower mean diversity than the other community types. The distance between trees was positively correlated to diversity, measured using the Shannon index, and to annual species richness and negatively correlated to woody cover in the understory. The variability in the distance between trees (associated with clumped distributions) was positively correlated to spatial heterogeneity, measured as Sb. The size of the trees had very little correlation to species diversity. As a whole, the results obtained show the difﬁculty involved in making generalised conclusions on the effects of disturbances on plant diversity
Keywords: annuals; Density; diversity; human intervention; land-use history; Oak trees; perennial herbs; Quercus pyrenaica; size; woody species

Forest structure and understory diversity in Quercus pyrenaica communities with different human uses and disturbances - Tárrega, Reyes; Calvo, Leonor; Marcos, Elena; Taboada, Ángela (Forest Ecology and Management, 2006)
The aim is to compare the diversity of the understory in Quercus pyrenaica communities according to the type of human intervention (grazing, obtaining wood or ﬁrewood, forest ﬁres). This interaction results in a modiﬁcation of the characteristics of the arboreal layer and shrub cover. Four types of oak communities were selected, each with ﬁve replicates: communities with a high density of shrubby oak (oak shrublands), open woodlands (‘‘dehesas’’), mature oak woods with abundant woody biomass in the understory and mature oak woods with little woody biomass in the understory. In each study site, we quantiﬁed the size of the trees (height, trunk perimeter and crown diameter) and their density, woody cover in the understory and species richness as well as diversity using the Shannon index, on both a small scale (per m 2 ) and for the total of each community. A clear difference was observed between the dehesas and the oak shrublands, the two community types with higher human intervention (the dehesas, with sustainable use for grazing and the oak shrublands, the most degraded due to repeated ﬁres), in the principal components analysis carried out with these variables. The other two community types, considered more mature forests, presented an intermediate location on the principal components analysis. However, there was no clear relationship between the different community types and the diversity values. No differences were observed in total species richness, except that the number of annuals being signiﬁcantly higher in the dehesas. Nor was it possible to detect any differences using the Shannon index, except for the oak shrublands which, although with a great variability among them, had a lower mean diversity than the other community types. The distance between trees was positively correlated to diversity, measured using the Shannon index, and to annual species richness and negatively correlated to woody cover in the understory. The variability in the distance between trees (associated with clumped distributions) was positively correlated to spatial heterogeneity, measured as Sb. The size of the trees had very little correlation to species diversity. As a whole, the results obtained show the difﬁculty involved in making generalised conclusions on the effects of disturbances on plant diversity
Keywords: annuals; Density; diversity; human intervention; land-use history; Oak trees; perennial herbs; Quercus pyrenaica; size; woody species

SEASONAL ABUNDANCE OF MILLIPEDES IN A MEDITERRANEAN OAK FOREST (SOUTHERN FRANCE) - David, J F (ISRAEL JOURNAL OF ZOOLOGY, 1995)
The millipede community of a helm oak forest (Quercus ilex) in southern France was sampled seasonally for 2 yr, at two depths in the forest floor. Despite the strong seasonality of climatic conditions, both recruitment periods and vertical displacements in the soil change markedly according to species; contrasting examples are provided by Glomeris marginata, which breeds in summer and burrows in winter, and by Opisthocheiron elegans, which behaves the opposite way. At the community level, biomass changes significantly between a spring minimum and an autumn maximum. Such a pattern results from the high abundance of G. marginata, a drought-resisting species which grows and reproduces during summer but experiences substantial winter mortality. The seasonal pattern is different in number of individuals due to the minute litter-dweller Polyxenus lagurus, which has a low population density in early autumn. The biomass of macrosaprophagous millipedes on the site (annual mean of 10.5 g live weight m(-2); autumn peak of 14.6 g live weight m(-2)) is much higher than that recorded further north in Europe, and its significance for litter consumption in Mediterranean forest is discussed.
Keywords: Bioclimatic limit; Elevation gradient; Oak trees; Regeneration; Shrub encroachment; Species distribution

SEASONAL ABUNDANCE OF MILLIPEDES IN A MEDITERRANEAN OAK FOREST (SOUTHERN FRANCE) - DAVID, J. F. (ISRAEL JOURNAL OF ZOOLOGY, 1995)
The millipede community of a helm oak forest (Quercus ilex) in southern France was sampled seasonally for 2 yr, at two depths in the forest floor. Despite the strong seasonality of climatic conditions, both recruitment periods and vertical displacements in the soil change markedly according to species; contrasting examples are provided by Glomeris marginata, which breeds in summer and burrows in winter, and by Opisthocheiron elegans, which behaves the opposite way. At the community level, biomass changes significantly between a spring minimum and an autumn maximum. Such a pattern results from the high abundance of G. marginata, a drought-resisting species which grows and reproduces during summer but experiences substantial winter mortality. The seasonal pattern is different in number of individuals due to the minute litter-dweller Polyxenus lagurus, which has a low population density in early autumn. The biomass of macrosaprophagous millipedes on the site (annual mean of 10.5 g live weight m(-2); autumn peak of 14.6 g live weight m(-2)) is much higher than that recorded further north in Europe, and its significance for litter consumption in Mediterranean forest is discussed.
The following values have no corresponding Zotero field: pub-location: PO BOX 50257, JERUSALEM 91502, ISRAEL publisher: LASER PAGES PUBL LTD
Keywords: Bioclimatic limit; Elevation gradient; Oak trees; Regeneration; Shrub encroachment; Species distribution